PENINGKATAN HASIL BELAJAR SISWA PADA MATERI IKATAN KIMIA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) BERBANTUAN MODUL DI KELAS X SMA NEGERI 10 AMBON - Dominggus Tahya (Molluca Journal of Chemistry Education (MJoCE), 2020)
Research has been conducted to determine student learning outcomes in chemical bonding material by applying the cooperative learning model type Numbered Head Together (NHT) with the help of modules, in class X students of SMA Negeri 10 Ambon. This type of research is quantitative descriptive. Based on the analysis of the data obtained 12 students (40%) get very good qualifications, 10 students (33.3%) get good qualifications, 6 students (20%) get enough qualifications, and 2 students (6.7%) get less qualifications. The acquisition of N-gain value is 18 students (60%) in the high category and 12 students (40%) are in the medium category. The results of the normalized gain score analysis of the average of all students amounted to 0.71 are in the high category. These results indicate that the application of the NHT (numbered heads together) cooperative learning model with the help of modules succeeded in improving student learning outcomes in all aspects (cognitive, affective, and psychomotor)